Double-counting of investment - Robert J. Barro (American Enterprise Institute (AEI), 2019)
The double-counting issue implies overstatement of levels of gross domestic product and national income. A proposed alternative measure of product and income involves a form of full expensing for gross investment.
Keywords: A; 330; investment; GDP